Liver Disease Among Mexican Americans Aged 67 Years and Older - Ronan P. Allencherril; Kyriakos S. Markides; Soham Al Snih (Journal of Primary Care & Community Health, 2022)
Background: The Center for Disease Control and Prevention (CDC) reports that liver disease is a significant cause of morbidity and mortality in the US, afflicting 4.5 million people in 2018, or approximately 1.7% of the American adult population. Objective: To determine the prevalence and risk factors associated with liver disease among older Mexican Americans over 18 years of follow-up. Methods: Non-institutionalized Mexican Americans aged ≥67 years (N = 1938) from the Hispanic Established Population for the Epidemiologic Study of the Elderly (1995/96-2012/13) were studied. Measures included socio-demographic variables, self-reported liver disease, language of interview, medical conditions, hand-grip strength, physical and cognitive function, depressive symptoms, and body mass index. Generalized estimating equation models were used to estimate the odds ratio and 95% confidence interval (CI) of liver disease over time. Results: The mean age at baseline was 74.9 ± 6.0 years and 58.4% were female. The prevalence of liver disease ranged from 2.4% to 8.4%. Over time, the odds ratio of reporting liver disease was 1.17 (CI = 1.12-1.22). Older age, Spanish interview, arthritis, diabetes, heart failure, cancer, and high scores on the Mini-Mental-State-Examination were factors associated with greater odds of reporting liver disease over time. Married participants reported lower odds of liver disease over time. Conclusions: The prevalence of liver disease in this population was high, ranging from 2.4% to 8.4%. Diabetes, heart failure, arthritis, and cancer were risk factors for liver disease. Screening for liver function among patients with these morbidities may help prevent liver disease in this population with high rates of diabetes and obesity.